Development of an electronic learning progression dashboard to monitor student clinical experiences. Issue 6 (6th January 2022) - Lai, Hollis; Ameli, Nazila; Patterson, Steven; Senior, Anthea; Lunardon, Doris
Abstract: Introduction: Clinical experience tracking mechanisms for students at dental schools provide patient assignment, student experience, and learning progression feedback. The purpose of this study was to evaluate dental students' clinical experiences following the implementation of a learning progression dashboard (LPD). Methods: After developing and deploying an electronic LPD using PHP, secondary data analysis on dental students' clinical experiences from 2017–2019 was conducted. Student experience differences were compared between the year before continuous use of the LPD and the first year using it. LPD data contained the required clinical procedures dentistry students must perform across all disciplines and the number of planned, in progress, and completed tasks each student has accomplished. Using two time points, the students' experiences were compared. Univariate statistics and independent t ‐tests were conducted in R for detecting the differences in the number and categories of codes. Results: The number and category of codes showed significant differences between the academic year 2017–2018 and 2018–2019 for both third‐ and fourth‐year dental students after one and two terms. Overall, students recorded a 26% greater number of treatment codes and experienced a 26% greater number of code categories compared to the previous year. Conclusion: Applying information management methods such as dashboards can better inform educators on student clinical experiences and improve clinical learning outcomes for students.